Residential Segregation and Adequate Housing among Migrants from Bolivia and Peru in Córdoba, Argentina - Florencia MOLINATTI; Enrique PELÁEZ (El Colegio de la Frontera Norte, A.C., 2017)
In a large part of Latin America, residential segregation has been examined almost exclusively from a socioeconomic perspective, with an ethnic approach far less common. The aim of this article is to analyze segregation of Bolivian and Peruvian migrants residing in the city of Córdoba and its association with access to adequate housing, based on data from the 2010 Census. Both groups are segregated and in deficient residential conditions. Although the most segregated group does not present the worst residential indicators, it is a paradox which underscores the complex relationship between segregation and access to adequate housing.